Principles of microeconomics brief edition - Frank, Robert H. (McGraw-Hill, 2011)
Two well-respected writers and researchers, Bob Frank and Ben Bernanke, have shown that the less-is-more approach affords similar gains in introductory economics. The authors introduce a coherent short list of core principles and reinforce them by illustrating and applying each in numerous contexts.